User arrival rate dependent profit maximisation of web application deployment on cloud. (10th January 2022) - Neelima, N.; Rao, B. Basaveswara; Rao, K. Gangadhara; Chandan, K.
The user arrival rate dependent profit maximisation is derived for cloud service provider (CSP) when web applications are deployed on the cloud for various instances of VM's operated using multi server queueing model. For any web application deployment on cloud, investigating the influence of user arrival rate to ensure accurate and productive usage of data to attain maximum profits is necessary. This paper is to find the profit maximisation with user arrival rate, keeping in mind the view of the dynamical changes of user requirements and attraction of the charges. The user request rate is independent of the configurable parameters like buffer size, number of VM's, and speed of the VM. To reach this objective, the finite multi-server profit queuing model is adopted and derived maximum profit through partial derivative with combination of bisection search method. Then sensitive analysis is processed and numerical illustrations are presented.